P. B. Struve’s Activities as Minister of Foreign Affairs of the Government of the South of Russia (1920) - A. A. Chemakin (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the activities of P. B. Struve as head of the foreign relations department of the government of the South of Russia in the spring and autumn of 1920. It is indicated that Struve, having become one of the closest assistance of Baron P. N. Wrangel, pursued a “leftist policy with his right hands” and played an important role in the recognition of the Crimea by the French authorities. Various stages of Struve’s activity in his post, connected both with his stay in the Crimea and with trips to Western Europe, are consistently considered. Using various sources, primarily press materials and memoirs of contemporaries, the author clarifi some important aspects of Struve’s activities at the head of the Crimean Foreign Ministry, as well as his position on Polish and Ukrainian issues. Criticism of Struve’s activities by the National Bolsheviks and “defeatists” who advocated an alliance with Poland against Soviet Russia is presented. According to the author of the article, despite the fact that Struve’s views on foreign and domestic policy have undergone certain changes (especially in comparison with the statements he made at the turn of 1919-1920), the basis of his views remained unchanged.